Genetic Improvement for Resistance to Black Sigatoka in Bananas: A Systematic Review - Soares, Julianna M. S.; Rocha, Anelita J.; Nascimento, Fernanda S.; Santos, Adriadna S.; Miller, Robert N. G.; Ferreira, Cláudia F.; Haddad, Fernando; Amorim, Vanusia B. O.; Amorim, Edson P. (Frontiers in Plant Science, 2021)
Bananas are an important staple food crop in tropical and subtropical regions in Asia, sub-Saharan Africa, and Central and South America. The plant is affected by numerous diseases, with the fungal leaf disease black Sigatoka, caused by Mycosphaerella fijiensis Morelet [anamorph: Pseudocercospora fijiensis (Morelet) Deighton], considered one of the most economically important phytosanitary problem. Although the development of resistant cultivars is recognized as most effective method for long term control of the disease, the majority of today´s cultivars are susceptible. In order to gain insights into this pathosystem, this first systematic literature review on the topic is presented. Utilizing six databases (PubMed Central, Web of Science, Google Academic, Springer, CAPES and Scopus Journals) searches were performed using pre-established inclusion and exclusion criteria. From a total of 3070 published studies examined, 24 were relevant with regard to the Musa-P. fijiensis pathosystem. Relevant papers highlighted that resistant and susceptible cultivars clearly respond differently to infection by this pathogen. From the sequenced reference genome of Musa acuminata, along with transcriptome, proteome and biochemical data, candidate genes and molecules have been identified for further validation through genetic transformation and gene editing approaches, however, the function of many genes found in the genome is still unknown. The papers also revealed gene-derived markers in Musa applicable for downstream application in marker assisted selection. The information gathered in this review furthers understanding of the immune response in Musa to the pathogen P. fijiensis and is relevant for genetic improvement programs for bananas and plantains for control of black Sigatoka